2022
DOI: 10.5530/ijper.56.1s.49
|View full text |Cite
|
Sign up to set email alerts
|

In silico Evaluation of Selected Compounds from Bergenia ciliata (Haw.) Sternb against Molecular Targets of Breast Cancer

Abstract: Background: A daunting public health issue that mainly affects women is breast cancer. Resistance to drugs applied in the treatment of this cancer as well as their side effects have made it necessary to look for new therapeutic agents. Objectives: The study is aimed at identification of multi-targeted inhibitors of molecular targets associated with breast cancer. Methods: We investigated fifteen compounds from Bergenia ciliata (haw.) Sternb against four major molecular targets of breast cancer viz; estrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Using molecular docking simulation and an in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) approach, Spriha et al [ 42 ] in their recent investigation aimed to identify some selected agents isolated from the multipotent plant Bergenia ciliate able to inhibit molecular targets involved in breast cancer, including PR (progesterone receptor), ER-α (estrogen receptor-α), EGFR (epidermal growth factor receptor), and HER2 (human epidermal growth factor receptor 2). Among the fifteen components analyzed, the results obtained from the molecular docking showed that stigmasterol has stronger binding affinities −9.4, −9.4, −10, and −8.8 kcal/mol towards ER-α, PR, HER2, and EGFR, respectively.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using molecular docking simulation and an in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) approach, Spriha et al [ 42 ] in their recent investigation aimed to identify some selected agents isolated from the multipotent plant Bergenia ciliate able to inhibit molecular targets involved in breast cancer, including PR (progesterone receptor), ER-α (estrogen receptor-α), EGFR (epidermal growth factor receptor), and HER2 (human epidermal growth factor receptor 2). Among the fifteen components analyzed, the results obtained from the molecular docking showed that stigmasterol has stronger binding affinities −9.4, −9.4, −10, and −8.8 kcal/mol towards ER-α, PR, HER2, and EGFR, respectively.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…In addition, in silico ADMET properties revealed that stigmasterol was identified as a substrate for P-glycoprotein and CYP3A4. It demonstrated high permeability for human intestinal absorption and Caco-2 cells, as well as high blood–brain barrier permeability, and showed no carcinogenicity [ 42 ]. Based on these data, stigmasterol showed significant properties to be an excellent compound in the search for new multi-targeted drugs to prevent breast cancer.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking was performed using AutoDock 4.2. version. 27 AutoDock method combines energy evaluation through precalculated grids of affinity potential employing various search algorithms to find the suitable binding position for a ligand on a given protein (human PCYT). All rotatable bonds (rb) in the selected ligands were kept free to allow for flexible docking.…”
Section: Docking Studiesmentioning
confidence: 99%
“…27 Docking protocol validation procedure was executed by re-docking the respective native ligands in the binding sites of the proteins. 28 The target proteinligand docking was accomplished using AutoDock Vina (version 1.1.2). 29 In docking simulation, centers of the grids were located at the active site of respective proteins.…”
Section: Molecular Docking Analysis and Lipinski's Rule Of Five Predi...mentioning
confidence: 99%